2010
DOI: 10.4028/www.scientific.net/amr.156-157.973
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Palladium Based Catalysts by Electroless Plating and their Application in Catalytic Combustion of Toluene

Abstract: The palladium based combustion catalysts on FeCrAl alloy substrate (Pd/FeCrAl) were prepared by electroless plating method. By means of scanning electron microscopy (SEM), X-ray diffraction and BET specific surface area, it was found that the prepared catalyst after calcination treatment at 800°C could obtain utmost PdO phases, which were well dispersed on substrate with small and uniform particles. The EDX analysis and the adherence tests further indicated that a synergistic interaction was formed between pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was found that the catalytic performance of Pd/SSWM catalysts firstly increased and then decreased when the calcination temperature increased from 400℃ to 800℃. This varying trend could be attributed to the following reason: when the calcination temperature increased over 500℃, the Pd phases were then converted to PdO phases which were main active component for catalytic combustion of toluene [4]; and the reason that catalytic performance over catalyst calcined at 800℃ decreased significantly might be caused by the flaking of the Pd membrane and lead to the loss of active component.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the catalytic performance of Pd/SSWM catalysts firstly increased and then decreased when the calcination temperature increased from 400℃ to 800℃. This varying trend could be attributed to the following reason: when the calcination temperature increased over 500℃, the Pd phases were then converted to PdO phases which were main active component for catalytic combustion of toluene [4]; and the reason that catalytic performance over catalyst calcined at 800℃ decreased significantly might be caused by the flaking of the Pd membrane and lead to the loss of active component.…”
Section: Resultsmentioning
confidence: 99%